Ultrasonic-Assisted Pelleting of Sorghum Stalk: Predictive Models for Pellet Density and Durability Using Multiple Response Surface Methodology - Qi Zhang; Zhenzhen Shi; Pengfei Zhang; Meng Zhang; Zhichao Li; Xi Chen; Jiping Zhou (Energies, 2018)
In the field of renewable energy, feedstock such as cellulosic biomass has been proposed as a renewable source of fuel to produce energy. However, the use of raw biomass as feedstock causes high costs in handling, transportation, and storage. Compressing raw cellulosic biomass into pellets significantly increases the density and durability of cellulosic biomass, reducing the transportation and handling costs of feedstock. To ensure high pellet quality, high pellet density and durability are desired during a compressing process. In this study, ultrasonic vibration-assisted (UV-A) pelleting, as a novel pelleting method, was applied to measure pellet density and durability during experiments. Response surface methodology (RSM) was employed to investigate the effects of pelleting time, ultrasonic power, and pelleting pressure on the pellet density and pellet durability. The model was validated by comparing the predictive results with experimental data and demonstrated a good predictive ability (R2 > 0.95). By employing a Derringer and Suich’s desirability function, our results suggest that the optimal pellet density and durability are 1239 kg/m3 and 93%, respectively, when the pelleting time was set to 44 s, the ultrasonic power was set to 50%, and pressure was set to 42 psi (289,580 Pa).